Using Strategy Analytics To Measure Corporate Performance And Business Value Creation - Sandeep Kautish (Igi Global Hershey, PA, 2021)
This book provides concepts of strategic analytics and strategic analytics applications in each area of management i.e. market dynamics, customer analysis, operations, and people management with the goal of presenting best industry practices for turning managers into quantitative analysts or quantitative analysts and finally into expert strategists.
index
Keywords: Management Information Systems